Secondary batteries
Patent Information
- Application Number
- JP2025062249
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
Smart Images

Figure 2026168808000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to secondary batteries.
Background Art
[0002] In recent years, secondary batteries such as lithium ion secondary batteries capable of repeated charge and discharge have been used as portable power sources for mobile terminals and the like, and as vehicle drive power sources for electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV) and the like.
[0003] A secondary battery includes, as an electrode body, an assembly containing electrodes (a positive electrode and a negative electrode) that bear the battery reaction during charge and discharge. The positive electrode has, for example, a sheet-shaped current collector and a positive electrode active material layer on the current collector. The positive electrode is produced, for example, by applying an electrode slurry for positive electrode to both surfaces of the current collector, and then drying and pressing the coating film formed thereby. The electrode slurry contains a particulate positive electrode active material as a main component. By drying, the liquid component is removed from the coating film on the current collector to form the positive electrode active material layer. For the pressing, for example, a pair of press rolls is used. By pressing between the press rolls, the positive electrode active material layer is compressed in the thickness direction on the current collector, and a higher capacity density of the positive electrode is achieved. Such a technique related to secondary batteries is described, for example, in Patent Document 1 below.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0005] During the pressing process in the manufacturing of the positive electrode, a large load is applied to the positive electrode active material layer on the current collector. This can cause cracks (press cracks) in the positive electrode active material particles within the layer. New exposed surfaces (newly formed surfaces) are created at the locations of the press cracks in the positive electrode active material particles, and gas may be generated due to contact between these surfaces and the electrolyte during, for example, high-temperature storage tests of the secondary battery. Such gas generation is undesirable as it can cause deterioration of the battery, such as its capacity.
[0006] This disclosure was conceived under these circumstances and aims to provide a secondary battery suitable for reducing gas generation at the positive electrode while ensuring energy density. [Means for solving the problem]
[0007] The secondary battery disclosed herein comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode comprises a current collector and a positive electrode active material layer on the current collector. The positive electrode active material layer includes a first layer and a second layer, with the first layer located between the current collector and the second layer. The first layer contains first positive electrode active material particles. The second layer contains second positive electrode active material particles. The average particle strength of the second positive electrode active material particles is higher than the average particle strength of the first positive electrode active material particles and is 190 MPa or higher. The average circularity of the second positive electrode active material particles is 0.95 or higher. A secondary battery with such a configuration is suitable for reducing gas generation at the positive electrode while ensuring energy density. The reason for this is thought to be as follows.
[0008] In the positive electrode active material layer of the above-mentioned secondary battery (including the first and second layers in that order from the current collector side), as described above, the average particle strength of the second positive electrode active material particles in the second layer is higher than the average particle strength of the first positive electrode active material particles in the first layer, and is 190 MPa or higher. This helps to suppress press cracking of the positive electrode active material particles in the second layer (closer to the press roll than the first layer), where the load from the press roll (press load) tends to be more concentrated than in the first layer, in the pressing process described above for the conventional technology. Suppression of press cracking in the positive electrode active material particles (suppression of the generation and increase of newly formed surfaces as described above) is suitable for reducing the generation of the above-mentioned gas.
[0009] Furthermore, as described above, the average circularity of the second positive electrode active material particles in the second layer is 0.95 or higher. This helps to ensure slipperiness between the second positive electrode active material particles in the second layer, and therefore helps to alleviate the press load acting on the second positive electrode active material particles. Alleviating the press load on the second positive electrode active material particles helps to suppress press cracking of the particles and reduce the generation of the aforementioned gases.
[0010] In addition, the first layer of the positive electrode active material layer contains first positive electrode active material particles that are flexible because their average particle strength is lower compared to the second positive electrode active material particles in the second layer. This means that in the pressing process described above, the first layer acts as a cushion between the current collector and the second layer, helping to alleviate the pressing load applied to the second layer. Reducing the pressing load on the second layer helps to suppress press cracking of the positive electrode active material particles in the second layer and reduce the generation of the aforementioned gas.
[0011] Furthermore, the first positive electrode active material particles, having lower average particle strength compared to the second positive electrode active material particles, are more flexible and therefore more easily deformed by press loads and have higher packing properties (easier to densify) than the second positive electrode active material particles. Having a first layer containing such positive electrode active material particles in the positive electrode active material layer is suitable for ensuring a high capacity density in the positive electrode active material layer or the positive electrode, and therefore is suitable for ensuring a high energy density in a secondary battery.
[0012] As described above, the secondary battery with the above configuration is suitable for reducing the amount of gas generated at the positive electrode while ensuring energy density.
[0013] Preferably, the average particle strength of the first positive electrode active material particles is 160 MPa or less. This configuration is preferable in ensuring the aforementioned cushioning function of the first layer in the positive electrode active material layer and the aforementioned packing properties of the first positive electrode active material particles.
[0014] Preferably, the second positive electrode active material particles have a surface layer enriched with at least one element selected from the group consisting of Group 6 and Group 13 elements.
[0015] Preferably, the proportion of the above elements, selected from Group 6 and Group 13 elements, to the total amount of Ni, Co, and Mn in the second positive electrode active material particles is 0.8 mol% or more and 3.0 mol% or less. The above elements, selected from Group 6 and Group 13 elements, are preferably tungsten. These configurations are suitable for achieving high average particle strength for the second positive electrode active material particles.
[0016] Preferably, the proportion of the elements selected from Group 6 and Group 13 elements to the total amount of Ni, Co, and Mn in the first positive electrode active material particles is less than 0.8 mol%. Such a configuration is preferable in ensuring the aforementioned cushioning function of the first layer in the positive electrode active material layer and the aforementioned packing properties of the first positive electrode active material particles.
[0017] Preferably, the ratio of the thickness of the second layer to the total thickness of the positive electrode active material layer is 5% to 65%. This configuration is preferable for achieving a good balance between ensuring energy density in the positive electrode and reducing gas generation.
[0018] Preferably, the average particle size D of the first positive electrode active material particles. 50 The particle size is between 5 μm and 18 μm. Such a configuration is preferable for ensuring the aforementioned cushioning function of the first layer in the positive electrode active material layer and the aforementioned packing properties of the first positive electrode active material particles.
[0019] Preferably, the average particle size D of the second positive electrode active material particles. 50 The particle size is between 3 μm and 15 μm. Such a configuration is preferable for ensuring the packing of the second positive electrode active material particles in the second layer.
[0020] Preferably, the positive electrode active material constituting the first positive electrode active material particles and / or the second positive electrode active material particles has the compositional formula Li(Li a Ni x Co y Mn z M α This is a lithium composite oxide having a composition represented by O2 [wherein -0.1≦a≦0.1, 0.7≦x≦1, 0≦y≦0.3, 0≦z≦0.3, x+y+z=1, 0≦α≦0.1, and M is at least one element selected from the group consisting of B, Al, Mg, Ca, Ti, V, Cr, Ga, Zr, Nb, Mo, In, Hf, Ta, W, Tl]. Lithium composite oxides with such a composition are suitable for achieving high energy density as positive electrode active materials in secondary batteries. [Brief explanation of the drawing]
[0021] [Figure 1] This is a schematic cross-sectional view showing the internal structure of a secondary battery, which is one embodiment of the present invention. [Figure 2] Figure 1 is a schematic diagram showing the configuration of the electrode body of a secondary battery. [Figure 3] Figure 2 is a schematic cross-sectional view of the positive electrode of the electrode body, with a portion of the cross-section omitted. [Modes for carrying out the invention]
[0022] Hereinafter, a lithium-ion secondary battery will be described as one embodiment of the secondary battery of the present invention with reference to the drawings. Matters other than those specifically mentioned herein but necessary for carrying out the present invention (for example, the general configuration and manufacturing process of secondary batteries that do not characterize the present invention) can be understood as design matters of those skilled in the art based on the prior art. The present invention can be carried out based on the contents disclosed herein and the common technical knowledge of the art. In the following drawings, the same reference numerals are used to denote members and parts that perform the same function. Also, the dimensional relationships (length, width, thickness, etc.) in each figure do not reflect the actual dimensional relationships. In this specification, "secondary battery" refers to a general energy storage device that can be repeatedly charged and discharged, and is a term that includes so-called storage batteries and energy storage elements such as electric double-layer capacitors.
[0023] Figure 1 is a schematic cross-sectional view showing the internal structure of a secondary battery 100, which is one embodiment of the present invention. The secondary battery 100 comprises a battery case 110, an electrode body 120, a positive electrode terminal 130, a negative electrode terminal 140, and a non-aqueous electrolyte (not shown). In this embodiment, the secondary battery 100 is a lithium-ion secondary battery.
[0024] The battery case 110 is the housing of the secondary battery 100 and contains the electrode body 120 and the non-aqueous electrolyte. In this embodiment, the battery case 110 has a flat and rectangular parallelepiped shape (e.g., rhombus). Examples of materials that can be used to construct the battery case 110 include aluminum, aluminum alloy, iron, and iron alloy. From the viewpoint of achieving both weight reduction and the required rigidity of the battery case 110, the material that can be used to construct the battery case 110 is preferably aluminum or an aluminum alloy.
[0025] In this embodiment, the battery case 110 has a safety valve 111. In this embodiment, the safety valve 111 is located on the upper surface of the battery case 110 in Figure 1, between the positive terminal 130 and the negative terminal 140. The safety valve 111 is a thin-walled portion configured to rupture when the gas pressure inside the battery case 110 rises above a predetermined value. The rupture of the safety valve 111 releases the gas inside the battery case 110 to the outside, preventing or suppressing further pressure rise inside the battery case 110. The battery case 110 also has an injection hole (not shown) for injecting a non-aqueous electrolyte into the battery case 110. The injection hole is sealed by a sealing member after the non-aqueous electrolyte is injected.
[0026] Figure 2 is a schematic diagram showing the configuration of the electrode body 120. The electrode body 120 includes a laminated structure in which a positive electrode 10 and a negative electrode 20 are alternately arranged with a separator 30 in between. In this embodiment, the electrode body 120 is a flat wound electrode body, and is formed by winding up a laminated body of long sheets (having a width in a direction perpendicular to its longitudinal direction) in which a long sheet-shaped positive electrode 10, a long sheet-shaped separator 30, a long sheet-shaped negative electrode 20, and another long sheet-shaped separator 30 are arranged in this order. Alternatively, the electrode body 120 may be a laminated electrode body in which a rectangular positive electrode and a rectangular negative electrode are stacked in a state where they are insulated from each other.
[0027] The positive electrode 10 comprises a positive electrode current collector 11 and a positive electrode active material layer 12. In this embodiment, the positive electrode 10 has positive electrode active material layers 12 on both sides of the positive electrode current collector 11 (details will be described later with reference to Figure 3). As shown in Figure 2, the positive electrode current collector 11 has a portion 11a at one end (the left end in Figure 2) in the width direction W of the electrode body 120 or the positive electrode 10. The width direction W is the direction perpendicular to the longitudinal direction of the long sheet-like laminate. The portion 11a is a portion of the positive electrode current collector 11 in which the positive electrode active material layer 12 is exposed without being laminated. In the electrode body 120, which is a wound electrode body, the portion 11a is superimposed in the direction of lamination in the laminated structure of the electrode body 120 and functions as a current collector. The portion 11a is connected to the positive electrode current collector plate 131 in this superimposed and integrated state. Examples of materials for the positive electrode current collector plate 131 include aluminum and aluminum alloys. Examples of methods for connecting the positive electrode current collector plate 131 to portion 11a of the positive electrode 10 include ultrasonic bonding and laser welding.
[0028] The negative electrode 20 has a negative electrode current collector 21 and a negative electrode active material layer 22. In the present embodiment, the negative electrode 20 has the negative electrode active material layer 22 on both surfaces of the negative electrode current collector 21 (not shown). The negative electrode current collector 21 is preferably a strip-shaped conductive metal foil. Examples of the constituent material of the negative electrode current collector 21 include copper, copper alloys, nickel, and stainless steel, with copper foil being preferred. The negative electrode active material layer 22 includes a negative electrode active material capable of reversibly occluding and releasing charge carriers. Examples of the negative electrode active material include carbon materials such as graphite, hard carbon, and soft carbon. The graphite may be natural graphite or artificial graphite. The negative electrode active material may be a silicon-containing material. Examples of the silicon-containing material include silicon (Si), silicon oxide represented by SiOₓ (0.05<x<1.95), a Si-C composite containing Si particles in carbon particles, and lithium silicate (LiₓSiᵧO_z). The negative electrode active material layer 22 may contain additional components other than the negative electrode active material. Examples of the additive components include a binder and a thickener. Examples of the binder include rubbers such as styrene-butadiene rubber (SBR), and fluorine-based resins such as polyvinylidene fluoride (PVDF). Examples of the thickener include celluloses such as carboxymethyl cellulose (CMC).
[0029] The negative electrode current collector 21 has a portion 21a at the other end (the right end in the drawing) in the width direction W of the electrode body 120 or the negative electrode 20. The portion 21a is a partial region of the negative electrode current collector 21 that is exposed without the negative electrode active material layer 22 being laminated thereon. In the electrode body 120 which is a wound electrode body, the portion 21a is stacked in the lamination direction of the laminated structure of the electrode body 120 and functions as a current collecting portion. The portion 21a is connected to the negative electrode current collector plate 141 in such a stacked and integrated state. Examples of the constituent material of the negative electrode current collector plate 141 include copper and copper alloys. Examples of the connection method of the negative electrode current collector plate 141 to the portion 21a of the negative electrode 20 include ultrasonic bonding and laser welding.
[0030] The separator 30 is a component that insulates the positive electrode active material layer 12 and the negative electrode active material layer 22. The separator 30 is preferably a porous resin sheet made of polyolefin resin. Examples of polyolefin resins include polyethylene (PE) and polypropylene (PP). The surface of the separator 30 may be provided with a heat-resistant layer (HRL) containing an inorganic filler. Examples of constituent materials for the inorganic filler include alumina, boehmite, aluminum hydroxide, and titania.
[0031] As shown in Figure 1, the positive electrode terminal 130 is attached to the battery case 110. For example, the battery case 110 has a terminal opening that penetrates its constituent members (plate material) in the thickness direction, and the positive electrode terminal 130 is attached to this opening with an insulating gasket between it and the battery case 110. One method for attaching the positive electrode terminal 130 is crimping. The positive electrode terminal 130 is exposed both to the outside and inside of the battery case 110. Inside the battery case 110, the positive electrode terminal 130 is connected to the positive electrode current collector plate 131. The positive electrode terminal 130 is electrically connected to the positive electrode 10 of the electrode body 120 via the positive electrode current collector plate 131. Such a positive electrode terminal 130 is preferably made of metal, and more preferably of aluminum or an aluminum alloy.
[0032] The negative electrode terminal 140 is also attached to the battery case 110 (the method of attachment is the same as described above for the positive electrode terminal 130). The negative electrode terminal 140 is exposed to the outside of the battery case 110 and also to the inside of the battery case 110. Inside the battery case 110, the negative electrode terminal 140 is connected to the negative electrode current collector plate 141. The negative electrode terminal 140 is electrically connected to the negative electrode 20 of the electrode body 120 via the negative electrode current collector plate 141. Such a negative electrode terminal 140 is preferably made of metal, and more preferably of copper or a copper alloy.
[0033] The non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte (supporting salt). Examples of non-aqueous solvents include ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The non-aqueous solvent may be used alone or in combination of two or more types. The electrolyte is a lithium salt, preferably a fluorine-containing lithium salt. Examples of fluorine-containing lithium salts include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium bis(fluorosulfonyl)imide (F2LiNO4S2). The electrolyte may be used alone or in combination of two or more types. Such a non-aqueous electrolyte is impregnated into the electrode body 120 within the battery case 110. Any excess non-aqueous electrolyte that is not impregnated into the electrode body 120 may be stored inside the battery case 110.
[0034] Figure 3 is a partially simplified schematic cross-sectional view of a long sheet-shaped positive electrode 10 in the width direction W. The positive electrode 10 has a positive electrode current collector 11 and positive electrode active material layers 12 arranged on both sides of the positive electrode current collector 11 in the thickness direction D. Each positive electrode active material layer 12 includes a first layer 12A and a second layer 12B. In each positive electrode active material layer 12, the first layer 12A is located between the positive electrode current collector 11 and the second layer 12B. In this embodiment, the first layer 12A is located on the positive electrode current collector 11, the second layer 12B is located on the first layer 12A, and the second layer 12B is the outermost layer of the positive electrode active material layer 12. In other embodiments, the positive electrode active material layer 12 may include other layers. The other layers may be located, for example, between the positive electrode current collector 11 and the first layer 12A.
[0035] Examples of the positive electrode current collector 11 include conductive metal foil and resin sheets with conductive metal layers on both sides. Examples of the conductive metal for the positive electrode current collector 11 include aluminum, aluminum alloy, nickel, titanium, and stainless steel, with aluminum being preferred. The thickness of the positive electrode current collector 11 is preferably 5 μm or more, more preferably 8 μm or more, from the viewpoint of ensuring the strength of the positive electrode current collector 11 and, consequently, the strength of the positive electrode 10. The thickness of the positive electrode current collector 11 is preferably 30 μm or less, more preferably 20 μm or less, from the viewpoint of reducing the volume occupied by the positive electrode current collector 11 and ensuring the volumetric energy density of the secondary battery 100.
[0036] The first layer 12A of the positive electrode active material layer 12 contains first positive electrode active material particles (first CAM particles). The first CAM particles are, for example, particles of a composite oxide (lithium composite oxide) containing lithium (Li) and other metallic elements.
[0037] The lithium composite oxide is preferably a nickel (Ni)-containing lithium composite oxide, and more preferably a high-Ni-containing lithium composite oxide with a Ni content of 70 mol% (ratio to metal elements other than Li) or more. Such a configuration is preferable for achieving high energy density in the secondary battery 100 at low cost. Examples of Ni-containing lithium composite oxides constituting the first CAM particles include lithium nickel-based composite oxides, lithium nickel-cobalt-based composite oxides, lithium nickel-manganese-based composite oxides, lithium nickel-cobalt-manganese-based composite oxides, lithium nickel-cobalt-aluminum-based composite oxides, and lithium iron-nickel-manganese-based composite oxides. These may be used individually or in combination of two or more types. From the viewpoint of ensuring a long cycle life, good thermal stability, and high energy density in the secondary battery 100, lithium nickel-cobalt-manganese-based composite oxide is preferred as the Ni-containing lithium composite oxide.
[0038] The positive electrode active material constituting the first CAM particles (first positive electrode active material) preferably has a composition represented by the following composition formula (1).
[0039] Li(Li a Ni x Co y Mn z M α )O2(1) [In the formula, -0.1≦a≦0.1, 0.7≦x≦1, 0≦y≦0.3, 0≦z≦0.3, x+y+z=1, 0≦α≦0.1, and M is at least one element selected from the group consisting of B, Al, Mg, Ca, Ti, V, Cr, Ga, Zr, Nb, Mo, In, Hf, Ta, W, and Tl]
[0040] In Composition Formula (1), a satisfies -0.1≦a≦0.1, and preferably satisfies 0≦a≦0.1. From the viewpoint of achieving high energy density at low cost in the secondary battery 100, x satisfies 0.7≦x≦1, preferably satisfies 0.75≦x≦1, and more preferably satisfies 0.8≦x≦1. From the viewpoints of enhancing the structural stability of the positive electrode active material and reducing resistance, y satisfies 0≦y≦0.3, and preferably satisfies 0.1≦y≦0.3. From the viewpoints of enhancing the structural stability of the positive electrode active material and reducing cost, z satisfies 0≦z≦0.3, and preferably satisfies 0.1≦z≦0.3. The composition of the positive electrode active material (the first positive electrode active material and the second positive electrode active material described later) can be confirmed by, for example, high-frequency inductively coupled plasma (ICP) emission spectrometry.
[0041] Examples of the crystal structure of the Ni-containing lithium composite oxide include a layered rock salt type crystal structure and a spinel type crystal structure, and the layered rock salt type crystal structure is preferred. The crystal structure can be confirmed by, for example, X-ray crystal structure diffraction.
[0042] Examples of the shape of the first CAM particles include a substantially spherical shape, an ellipsoidal shape, and a flake shape, and the substantially spherical shape is preferred. As used in the present specification, the term "substantially spherical" refers to a shape that can be generally regarded as a sphere as a whole, and refers to a shape having an average aspect ratio (major axis / minor axis ratio) of approximately 1 to 2, for example, in the range of 1 to 1.5, based on a cross-sectional observation image with an electron microscope.
[0043] The average circularity of the first CAM particles is preferably 0.90 or higher, more preferably 0.91 or higher, and even more preferably 0.92 or higher, from the viewpoint of ensuring the packing of the first CAM particles in the first layer 12A. The average circularity of the first CAM particles is preferably 1.00 or lower, more preferably 0.99 or lower, and even more preferably 0.98 or lower, from the viewpoint of reducing the manufacturing cost of the secondary battery 100. As a method for adjusting the average circularity of the CAM particles (first CAM particles, second CAM particles described later), mechanical post-treatment can be used, for example. As a mechanical post-treatment, a method of grinding off the edges and corners of the particles using a ball mill or the like is preferred. In such a treatment, it is possible to increase the average circularity by extending the treatment time. The method for measuring the average circularity of the CAM particles is described later with respect to test examples.
[0044] Average particle size D of the first CAM particle 50 From the viewpoint of ensuring particle strength, the particle size is preferably 5 μm or larger, more preferably 7 μm or larger, and even more preferably 9 μm or larger. Average particle size D of the first CAM particles 50 From the viewpoint of ensuring the packing of the first CAM particles in the first layer 12A, the average particle size D is preferably 18 μm or less, more preferably 15 μm or less, and even more preferably 12 μm or less. 50 D is the median diameter in the volume-based particle size distribution (the particle size at which the volume cumulative frequency reaches 50% from the smallest diameter side), and can be determined, for example, based on the particle size distribution obtained by laser diffraction and scattering. 50 One method for adjusting the reaction conditions is to adjust the reaction conditions during the crystallization method described later to obtain a composite hydroxide as a cathode active material precursor. Examples of such conditions include the temperature, pH, stirring speed, various concentrations such as ammonium ion concentration in the reaction solution, and the reaction time.
[0045] The first CAM particle may be a primary particle, or it may be a secondary particle formed by the aggregation of multiple primary particles by physical or chemical bonding forces, preferably a secondary particle having gaps between aggregated primary particles inside.
[0046] The average particle strength of the first CAM particles is preferably 110 MPa or higher, more preferably 125 MPa or higher, and even more preferably 140 MPa or higher. Such a configuration is preferable for suppressing press cracking of the first CAM particles in the first layer 12A during the pressing process described later in the manufacturing process of the secondary battery 100. The average particle strength of the first CAM particles is preferably 160 MPa or lower, more preferably 155 MPa or lower, and even more preferably 150 MPa or lower. Such a configuration is preferable for ensuring the flexibility of the first CAM particles in the first layer 12A and achieving high filling during the pressing process described later in the manufacturing process of the secondary battery 100. The average particle strength of the first CAM particles can be determined as the average value of the crushing strength of the first CAM particles. The crushing strength of particles such as the first CAM particles can be measured, for example, using an ultra-fine indentation hardness tester (product name "ENT-5", manufactured by Elionix Co., Ltd.). The method for deriving the average particle strength of CAM particles (first CAM particles, second CAM particles described later) is as described later with respect to test examples. Methods for adjusting the average particle strength of CAM particles include, for example, adjusting the reaction conditions during the crystallization method described later to obtain the composite hydroxide as a cathode active material precursor. These conditions include, for example, the temperature, pH, stirring speed, various concentrations such as ammonium ion concentration in the reaction solution, and the reaction time. Other methods for adjusting the average particle strength of CAM particles include adjusting the calcination temperature of the CAM particles, and selecting the type and amount of coating element described later for the CAM particles.
[0047] The first CAM particle, like the second CAM particle described later, may have a surface layer enriched with at least one element selected from the group consisting of Group 6 and Group 13 elements. The enriched surface layer refers to the region within 20% of the particle surface from the outermost surface to the particle center, where the concentration of the aforementioned element (coating element) is higher than that of the particle center. The aforementioned element (coating element) may or may not be present in the particle center. Examples of Group 6 elements include Cr, Mo, and W, and examples of Group 13 elements include B, Al, Ga, In, and Tl. The ratio of the coating element to the total amount of Ni, Co, and Mn (Ni+Co+Mn) in the first CAM particle is preferably less than 0.8 mol%, preferably 0.7 mol% or less, and more preferably 0.6 mol% or less. In CAM particles (first CAM particles, second CAM particles described later), the higher the ratio of the coating element to the total amount of the above metal elements (Ni+Co+Mn), the higher the concentration of the coating element in the surface layer tends to be. Furthermore, for CAM particles (first CAM particles, second CAM particles described later) that contain the above-mentioned coating elements, the presence of the coating elements in the surface layer can be confirmed, for example, by LA-ICP-MS (Laser Ablation Inductively Coupled Plasma Mass Spectrometry) analysis.
[0048] The first layer 12A may contain additive components other than the first CAM particles. Examples of additive components include other positive electrode active material particles, conductive materials, binders, and trilithium phosphate. Examples of conductive materials include acetylene black, Ketjen black, graphite, and carbon nanotubes. Examples of binders include fluororesins such as polyvinylidene fluoride (PVDF) and rubbers such as styrene-butadiene rubber (SBR).
[0049] The second layer 12B of the positive electrode active material layer 12 contains second positive electrode active material particles (second CAM particles). The second CAM particles are, for example, particles of lithium composite oxide. The lithium composite oxide constituting the second CAM particles is preferably a Ni-containing lithium composite oxide, and more preferably a high-Ni-containing lithium composite oxide with a Ni content of 70 mol% (ratio to metal elements other than Li) or more. Such a configuration is preferable for achieving a high energy density in the secondary battery 100 at low cost. Examples of Ni-containing lithium composite oxides constituting the second CAM particles include the Ni-containing lithium composite oxides described above for the first CAM particles, and lithium nickel cobalt manganese-based composite oxides are preferred.
[0050] The positive electrode active material constituting the second CAM particles (second positive electrode active material) preferably has the composition represented by the above composition formula (1). The preferred abundance of elements in composition formula (1) is the same for the second CAM particles as described above for the first CAM particles. Furthermore, the crystal structure, particle shape, and particle aggregation manner (primary particles, secondary particles) of the second positive electrode active material constituting the second CAM particles are the same as those described above for the first positive electrode active material constituting the first CAM particles.
[0051] The average circularity of the second CAM particles is 0.95 or higher, preferably 0.96 or higher, and more preferably 0.97 or higher. These configurations help ensure slipperiness between the second CAM particles in the second layer 12B during the pressing process described later in the manufacturing process of the secondary battery 100, and thus help to alleviate the pressing load acting on the second CAM particles. The average circularity of the second CAM particles is 1.0 or lower, preferably 0.99 or lower, and more preferably 0.98 or lower, from the viewpoint of reducing the manufacturing cost of the secondary battery 100.
[0052] Average particle size D of the second CAM particle 50 From the viewpoint of ensuring particle strength, the average particle size D of the second CAM particle is preferably 3 μm or more, more preferably 4 μm or more, and even more preferably 5 μm or more. 50From the viewpoint of ensuring the packing of the second CAM particles in the second layer, the particle size is preferably 15 μm or less, more preferably 12 μm or less, and even more preferably 10 μm or less.
[0053] The average particle strength of the second CAM particles is higher than that of the first CAM particles described above. The average particle strength of the second CAM particles is preferably 190 MPa or higher, more preferably 200 MPa or higher, and even more preferably 210 MPa or higher. These configurations help suppress press cracking of the positive electrode active material particles in the second layer 12B (closer to the press roll than the first layer 12A) where the press load tends to concentrate more than in the first layer 12A during the press process described later in the manufacturing process of the secondary battery 100. The average particle strength of the second CAM particles is, for example, 300 MPa or less, 280 MPa or less, or 250 MPa or less.
[0054] The second CAM particle has a surface layer enriched with at least one element (coating element) selected from the group consisting of Group 6 and Group 13 elements. The concentration of the coating element in the surface layer of the second CAM particle is higher than the concentration of the coating element in the surface layer of the first CAM particle described above. The coating element is more preferably at least one element selected from the group consisting of W, Mo, Cr, B, Al, Ga, In, and Tl, and even more preferably W. The ratio of the coating element to the total amount of Ni, Co, and Mn (Ni+Co+Mn) in the second CAM particle is preferably 0.8 mol% or more, preferably 1.5 mol% or more, more preferably 1.9 mol% or more, and particularly preferably 2.2 mol% or more. The above configuration of the surface layer of the second CAM particle is suitable for achieving a high average particle strength for the second CAM particle. The ratio of the coating element to the total amount of metal elements (Ni+Co+Mn) in the second CAM particles is preferably 3.0 mol% or less, preferably 2.7 mol% or less, and more preferably 2.5 mol% or less, from the viewpoint of ensuring the energy density of the secondary battery 100.
[0055] The second layer 12B may contain additive components other than the second CAM particles. Examples of additive components include other positive electrode active material particles, conductive materials, binders, and trilithium phosphate, similar to those described above for the first CAM particles.
[0056] In this embodiment, the total thickness of the positive electrode active material layer 12 is the sum of the thickness of the first layer 12A and the thickness of the second layer 12B. The total thickness of the positive electrode active material layer 12 is preferably 30 μm or more, more preferably 40 μm or more, from the viewpoint of ensuring minimum handling characteristics as an electrode plate. The total thickness of the positive electrode active material layer 12 is preferably 100 μm or less, more preferably 90 μm or less, and even more preferably 80 μm or less, from the viewpoint of ensuring good rate characteristics in the secondary battery 100. The thickness of the first layer 12A is, for example, 15 μm or more, preferably 20 μm or more, for example 90 μm or less, and preferably 80 μm or less. The thickness of the second layer 12B is, for example 3 μm or more, preferably 5 μm or more, for example 50 μm or less, and preferably 40 μm or less.
[0057] The ratio of the thickness of the second layer 12B to the total thickness of the positive electrode active material layer 12 is preferably 5% or more, more preferably 8% or more, and even more preferably 10% or more, from the viewpoint of suppressing particle cracking in the second layer 12B where stress is concentrated when the positive electrode 10 is pressed. The ratio of the thickness of the second layer 12B to the total thickness of the positive electrode active material layer 12 is preferably 65% or less, more preferably 45% or less, and even more preferably 25% or less, from the viewpoint of ensuring energy density in the positive electrode 10.
[0058] The above-mentioned positive electrode active material particles (first and second CAM particles) can be fabricated, for example, as follows.
[0059] First, a composite hydroxide, which is a precursor of the positive electrode active material (lithium composite oxide), is obtained by crystallization. In the crystallization method, for example, a reaction solution with pH adjusted is stirred, and a raw material aqueous solution containing a predetermined metal salt is added dropwise to the reaction solution (crystallization reaction). The reaction solution is, for example, ion-exchanged water with a pH of 7. The raw material aqueous solution contains each metal salt, which is a source of each metal element (excluding the lithium and coating elements mentioned above) contained in the positive electrode active material to be produced, at a predetermined concentration. As the metal salt, depending on the composition of the positive electrode active material to be produced, for example, nickel salts, cobalt salts, and manganese salts can be used. As the nickel salt, for example, nickel sulfate, nickel nitrate, or nickel carbonate can be used. As the cobalt salt, for example, cobalt sulfate, cobalt nitrate, or cobalt carbonate can be used. As the manganese salt, for example, manganese sulfate, manganese nitrate, or manganese carbonate can be used. During the crystallization reaction, the reaction solution is kept at a temperature of, for example, 25°C, the pH is maintained at, for example, 10-13 by adding an alkaline aqueous solution (e.g., sodium hydroxide aqueous solution), and the ammonium ion concentration is controlled to 10-15 g / L by adding a basic aqueous solution containing ammonium ions (e.g., aqueous ammonia). This crystallization reaction precipitates (coprecipitation) the complex hydroxide, which is a precursor of the positive electrode active material. The resulting coprecipitation product (hydroxide particles) is filtered, washed with water, and dried. This yields a powder of the complex hydroxide, which is a precursor of the positive electrode active material.
[0060] Next, the obtained composite hydroxide powder and lithium hydroxide (LiOH) powder are dry-mixed in a predetermined ratio to prepare a mixed powder (preparation of the first mixed powder). Then, this mixed powder is subjected to calcination treatment, for example, under an atmospheric environment. The calcination temperature is, for example, 650°C to 900°C, and the calcination time is, for example, 9 to 15 hours. This yields a lithium composite oxide powder of a predetermined composition.
[0061] When adding the above-mentioned coating element to positive electrode active material particles, the obtained lithium composite oxide powder and the coating element oxide powder are then dry-mixed in a predetermined ratio to prepare a mixed powder (preparation of the second mixed powder). Examples of coating element oxides include tungsten oxide (e.g., WO3), boric acid, and aluminum oxide, depending on the type of coating element to be added. Next, this mixed powder is subjected to a firing treatment, for example, under an atmospheric environment. The firing temperature is, for example, 300°C, and the firing time is, for example, 1 to 3 hours. This yields positive electrode active material particles whose surfaces are enriched with the above-mentioned coating element.
[0062] To adjust the circularity of the positive electrode active material particles, the obtained positive electrode active material particles are subjected to ball milling using a ball milling device. In ball milling, the rotation speed is set to, for example, 100 to 200 rpm, the processing time to, for example, 1 to 2 hours, and the ball diameter (Φ) to, for example, 2 to 5 mm.
[0063] First positive electrode active material particles for forming the first layer 12A of the positive electrode 10 and second positive electrode active material particles for forming the second layer 12B can be produced, for example, by the method described above. In the production of the positive electrode 10 of the secondary battery 100, a first positive electrode slurry containing the first positive electrode active material particles and a second positive electrode slurry containing the second positive electrode active material particles are prepared. Examples of solvents for slurry preparation include N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), and isopropyl alcohol. The first positive electrode slurry and the second positive electrode slurry each contain the above-mentioned additive components (conductive materials and binders, etc.) other than the positive electrode active material particles as needed. Next, a positive electrode active material layer is formed on one side of the positive electrode current collector 11 by coating and drying the first positive electrode slurry and then coating and drying the second positive electrode slurry. Next, a positive electrode active material layer is formed on the other surface of the positive electrode current collector 11 by coating and drying a first positive electrode slurry, followed by coating and drying a second positive electrode slurry. Then, for example, by pressing between a pair of press rolls, the positive electrode active material layers on both sides of the positive electrode current collector 11 are compressed in the thickness direction to form a compacted (high capacity density) positive electrode active material layer 12 on both sides of the positive electrode current collector 11 (pressing process). In this way, the positive electrode 10 can be manufactured. The secondary battery 100 described above can be manufactured as having an electrode body 120 equipped with such a positive electrode 10 as the positive electrode responsible for the battery reaction during charging and discharging.
[0064] The secondary battery 100 is suitable for reducing the amount of gas generated at the positive electrode 10 while maintaining energy density. The reason is as follows:
[0065] In the positive electrode active material layer 12 of the secondary battery 100 (which includes the first layer 12A and the second layer 12B in that order from the positive electrode current collector 11 side), as described above, the average particle strength of the second CAM particles in the second layer 12B is higher than the average particle strength of the first CAM particles in the first layer 12A. This helps to suppress press cracking of the second CAM particles in the second layer 12B (closer to the press roll than the first layer 12A) where the load from the press roll (press load) is more concentrated than in the first layer 12A during the pressing process in the manufacturing process of the secondary battery 100. Suppressing press cracking in the second CAM particles suppresses the formation of new exposed surfaces (newly formed surfaces) on the second CAM particles and suppresses the generation of gas caused by contact between the newly formed surfaces and the non-aqueous electrolyte, etc.
[0066] Furthermore, as mentioned above, the average circularity of the second CAM particles in the second layer 12B is 0.95 or higher. This helps to ensure slipperiness between the second CAM particles in the second layer 12B, and therefore helps to alleviate the press load acting on the second CAM particles. Alleviating the press load on the second CAM particles helps to suppress press cracking of the particles and reduce the generation of the aforementioned gases.
[0067] In addition, the first layer 12A of the positive electrode active material layer 12 contains first CAM particles that are flexible because they have a lower average particle strength compared to the second CAM particles in the second layer 12B. This means that in the pressing process described above, the first layer 12A acts as a cushion between the positive electrode current collector 11 and the second layer 12B, helping to alleviate the press load applied to the second layer 12B. This alleviation of the press load on the second layer 12B helps to suppress press cracking of the second CAM particles in the second layer 12B and reduce the generation of the aforementioned gas.
[0068] Furthermore, the first CAM particles, having lower average particle strength compared to the second CAM particles, are more flexible and therefore more easily deformed by press loads and have higher packing properties (easier to densify) than the second CAM particles. Having the first layer 12A containing such first CAM particles in the positive electrode active material layer 12 is suitable for ensuring a high capacity density in the positive electrode active material layer 12 or the positive electrode 10, and therefore is suitable for ensuring a high energy density in the secondary battery 100.
[0069] As described above, the secondary battery 100 with the above configuration is suitable for reducing the amount of gas generated at the positive electrode 10 while ensuring energy density.
[0070] In the embodiments described above, the secondary battery 100 was described as a prismatic secondary battery equipped with a flat-shaped electrode body 120. However, the secondary battery disclosed herein may be a secondary battery of other shapes and forms. For example, the technology disclosed herein can also be applied to lithium-ion secondary batteries equipped with stacked electrode bodies, cylindrical lithium-ion secondary batteries, laminated lithium-ion secondary batteries, and the like.
[0071] [Example Test] The following describes test examples relating to the present invention, but the present invention is not intended to be limited to those shown in these test examples.
[0072] [Example 1] [Fabrication of the positive electrode] The cathode in Example 1 was fabricated by following the steps of creating the first cathode active material, the second cathode active material, and forming the cathode active material layer as described below.
[0073] <Preparation of the first positive electrode active material> In the preparation of the first positive electrode active material (first CAM), first, nickel-cobalt-manganese (NCM) composite hydroxide, a precursor of the first CAM, was obtained. Specifically, first, an aqueous solution of raw materials and a reaction solution were prepared. The reaction solution was prepared in a 5 L reaction vessel. The aqueous raw material solution contained nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of Ni:Co:Mn = 80:10:10, with a total concentration of these metal salts of 1.5 mol / L. The reaction solution was ion-exchanged water, which had undergone treatment to remove dissolved oxygen by aeration with an inert gas and adjustment of the pH (at 25°C) to 10.5-11.5 by adding an aqueous sodium hydroxide solution (during which the liquid temperature was maintained at 30°C). Next, while stirring the reaction solution (stirring speed 600 rpm), the aqueous raw material solution was added dropwise to the reaction solution, and the NCM composite hydroxide was precipitated (co-precipitated) by a crystallization reaction. The reaction solution being added dropwise was maintained at 25°C to 35°C, the pH was maintained at 10.5 to 11.5 by adding an aqueous sodium hydroxide solution, and the ammonium ion concentration was controlled to 10 g / L by adding an aqueous ammonia solution (crystallization was performed for 20 hours under these conditions). Next, the obtained coprecipitation product (hydroxide particles) was filtered and washed with water, then dried in an oven at 120°C to obtain a powder. This yielded NCM complex hydroxide (Ni), a precursor of the first CAM. 0.8 Co 0.1 Mn 0.1 (OH)2) powder was obtained.
[0074] Next, the obtained NCM composite hydroxide powder and lithium hydroxide (LiOH) powder were mixed in a molar ratio of Li:(Ni+Co+Mn)=1.05:1.00 to prepare a mixed powder (preparation of the first mixed powder). Then, this mixed powder was calcined under atmospheric conditions at 770°C for 15 hours (first calcination treatment). This yielded lithium composite oxide powder.
[0075] Next, the obtained lithium composite oxide powder and tungsten oxide (WO3) powder were mixed in a composition of (Ni+Co+Mn):W=1.000:0.005 to prepare a mixed powder (preparation of the second mixed powder). Next, this mixed powder was calcined under atmospheric conditions of 300°C for 3 hours (second calcination treatment). This yielded the first CAM powder. The particles in this powder were first CAM particles (Li) whose surfaces were enriched by tungsten. 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.005 )O2,W ratio: 0.5mol%, average particle size D 50 The thickness was 10 μm.
[0076] <Preparation of the second positive electrode active material> In the preparation of the second positive electrode active material (second CAM), first, a nickel-cobalt-manganese (NCM) composite hydroxide, which is a precursor of the second CAM, was obtained. Specifically, first, an aqueous solution of raw materials and a reaction solution were prepared. The reaction solution was prepared in a 5 L reaction vessel. The aqueous raw material solution contained nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of Ni:Co:Mn = 80:10:10, with a total concentration of these metal salts of 1.5 mol / L. The reaction solution was ion-exchanged water, which underwent treatment to remove dissolved oxygen by aeration with an inert gas and adjustment of the pH (at 25°C) to 12.0-12.5 by adding an aqueous sodium hydroxide solution (during which the liquid temperature was maintained at 30°C). Next, in the first step of crystallization, the reaction solution was stirred (stirring speed 500 rpm) and the first raw material aqueous solution was added dropwise to the reaction solution to precipitate (coprecipitation) the NCM complex hydroxide by crystallization. The reaction solution during the dropwise addition was maintained at 25°C to 35°C, the pH was maintained at 12.0 to 12.5 by adding sodium hydroxide aqueous solution, and the ammonium ion concentration was controlled to 10 g / L by adding ammonia water, and the crystallization time was set to 1 hour. Next, in the second step of crystallization, the pH of the reaction solution was adjusted to 10.5 to 11.5 by adding sulfuric acid dropwise, and then the NCM complex hydroxide was precipitated (coprecipitation) for 20 hours under the same conditions as in the first step. The obtained coprecipitation product (hydroxide particles) was filtered and washed with water, and then dried in an oven at 120°C to obtain a powder. This yielded the NCM complex hydroxide (Ni), which is a precursor of the second CAM. 0.8 Co 0.1 Mn 0.1 (OH)2) powder was obtained.
[0077] Next, the obtained NCM composite hydroxide powder and lithium hydroxide (LiOH) powder were mixed in a molar ratio of Li:(Ni+Co+Mn)=1.05:1.00 to prepare a mixed powder (preparation of the first mixed powder). Then, this mixed powder was calcined in an air atmosphere at 780°C for 4 hours, followed by calcination at 900°C for 5 hours (first calcination treatment). This yielded lithium composite oxide powder.
[0078] Next, the obtained lithium composite oxide powder and tungsten oxide (WO3) powder were dry-mixed in an automatic mortar and pestle to prepare a mixed powder (preparation of the second mixed powder). Next, this mixed powder was calcined under atmospheric conditions at 300°C for 3 hours (second calcination treatment). This yielded the second CAM powder. The particles in this powder were second CAM particles (Li) whose surfaces were enriched by tungsten. 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.010 ) O2, W ratio: 1.0 mol%, average particle size D 50 The particle size was 4.0 μm.
[0079] Next, ball milling was performed. Specifically, a ball milling apparatus (product name "Planetary Ball Mill Pulnerisette 5", manufactured by Fritsch) and zirconia balls (manufactured by Nikkatoh, average diameter 2 mm) were used as milling media, and ball milling of the second CAM was performed at a rotation speed of 100 rpm and a processing time of 1 hour. In this ball milling, the volume ratio of balls, sample, and excess space was adjusted to approximately 1:1:1, and the apparatus was stopped every 15 minutes to stir the sample and balls. This resulted in obtaining a powder of the second CAM with increased circularity. The particles in this powder were second CAM particles (Li(Li)) whose surfaces were enriched with tungsten. 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.01 The O2,W ratio was 1.0 mol%, and the average particle size D50 was 4.0 μm.
[0080] <Formation of the positive electrode active material layer> First, a positive electrode current collector and a first positive electrode slurry and a second positive electrode slurry for forming the first and second layers of the positive electrode active material layer (CAM layer) on the positive electrode current collector were prepared. The positive electrode current collector is 13 μm thick aluminum foil. The first positive electrode slurry was obtained by kneading a mixture containing the above-mentioned first CAM, carbon black (CB) as a conductive material, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio of 100:1.5:1, and further containing a predetermined amount of N-methyl-2-pyrrolidone (NMP) as a solvent. The second positive electrode slurry was obtained by kneading a mixture containing the above-mentioned second CAM, CB, and PVDF in a mass ratio of 100:1.5:1, and further containing a predetermined amount of NMP. Next, a CAM layer (first layer, second layer) was formed on one side of the positive electrode current collector by coating and drying the first positive electrode slurry, followed by coating and drying the second positive electrode slurry. Then, a CAM layer (first layer, second layer) was formed on the other side of the positive electrode current collector by coating and drying the first positive electrode slurry, followed by coating and drying the second positive electrode slurry. After that, the positive electrode current collector with the CAM layer was rolled using a rolling mill, with the CAM layer thickness being 70 μm and the density being 3.6 g / cm³. 3 The material was rolled to achieve the following (CAM layer rolling process). This resulted in a positive electrode with two CAM layers arranged on both sides of the positive electrode current collector. The ratio of the thickness of the second layer in each CAM layer was set to 10% (1st layer:2nd layer = 9:1 [thickness ratio], the ratio of the thickness of the second layer to the thickness of the first layer is 0.11).
[0081] The positive electrode in Example 1 was fabricated as described above. The positive electrode in Example 1 has a laminated structure consisting of a CAM layer (second layer / first layer) / positive electrode current collector (aluminum foil) / CAM layer (first layer / second layer).
[0082] [Fabrication of the negative electrode] First, a negative electrode current collector and a negative electrode slurry for forming a negative electrode active material layer (AAM layer) on the negative electrode current collector were prepared. The negative electrode current collector was a copper foil with a thickness of 8 μm. The negative electrode slurry was obtained by kneading graphite as the negative electrode active material (AAM), styrene-butadiene rubber (SBR) as a binder, and carboxymethylcellulose (CMC) as a thickener in ion-exchanged water in a mass ratio of AAM:SBR:CMC = 100:0.7:1. Next, the negative electrode slurry was applied to each of the two sides of the negative electrode current collector to form a coating, and then the coating was dried to form the AAM layer. Next, the negative electrode current collector with the AAM layer was rolled to a predetermined thickness using a rolling mill. In this way, the negative electrode in Example 1 was manufactured.
[0083] [Manufacturing of secondary batteries] First, the positive and negative electrodes were cut to obtain a positive electrode sheet (CAM layer / positive electrode current collector / CAM layer) and a negative electrode sheet (AAM layer / negative electrode current collector / AAM layer). A separator having a two-layer structure of polyethylene / heat-resistant layer was also prepared. Next, these were laminated in such a manner that the heat-resistant layer of the separator and the CAM layer of the positive electrode sheet were in contact and the positive electrode current collector was exposed to obtain a laminated electrode body. Next, the positive electrode current collector (aluminum foil) of the positive electrode sheet in this laminated electrode body was welded to the positive electrode lead (aluminum plate) for external current collection, and the negative electrode current collector (copper foil) of the negative electrode sheet was welded to the negative electrode lead (copper plate) for external current collection. Next, the electrode body of the laminated electrode body with leads was inserted into an outer casing (aluminum laminate film pouch), a non-aqueous electrolyte was injected into the outer casing, and after standing for 12 hours, the outer casing was sealed. The non-aqueous electrolyte contains a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (EC:EMC:DMC = 30:30:40 [volume ratio]), and LiPF6 (concentration: 1.15 mol / L) as an electrolyte that dissolves in it. This yielded a secondary battery (lithium-ion battery) for evaluation in Example 1. In this secondary battery, the stacked electrode body and the non-aqueous electrolyte are sealed inside an outer casing (pouch), with a portion of the tips of the positive and negative electrode leads of the stacked electrode body exposed outside the casing.
[0084] [Example 2] The secondary battery of Example 2 was fabricated in the same manner as the secondary battery of Example 1, except for the following: In the preparation of the second mixed powder for the second layer of the CAM layer, the W ratio in the second mixed powder was set to 2.0 mol%. The particles in the obtained second CAM powder were second CAM particles (Li(Li 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.02 ) O2, W ratio: 2.0 mol%, average particle size D 50 The particle size was 5.0 μm.
[0085] [Example 3] The secondary battery of Example 3 was fabricated using the same method as the secondary battery of Example 1, except for the method of fabricating the second positive electrode active material for the second layer of the CAM layer. The method of fabricating the second positive electrode active material in Example 3 is the same as the method of fabricating the first positive electrode active material in Example 1, except for the following (ball milling was not performed).
[0086] In the CAM precursor acquisition process, the stirring speed of the reaction solution during the crystallization reaction was set to 500 rpm. In the first calcination treatment, the calcination temperature was set to 800°C and the calcination time to 15 hours. The W content in the mixed powder was set to 2.5 mol%. The particles in the obtained second CAM powder were second CAM particles (Li(Li 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.025 )O2,W concentration: 2.5mol%, average particle size D 50 It was 12 μm.
[0087] [Example 4] The secondary battery of Example 4 was manufactured in the same manner as the secondary battery of Example 1, except that the preparation of the second mixed powder and the subsequent firing treatment were not performed in the preparation of the first CAM for the first layer.
[0088] [Example 5] The secondary battery of Example 5 was fabricated using the same method as the secondary battery of Example 1, except that the ratio of the thickness of the second layer to the thickness of each CAM layer (thickness 70 μm) was set to 50% during the formation of the CAM layer.
[0089] [Example 6] The secondary battery of Example 6 was fabricated in the same manner as the secondary battery of Example 1, except for the following: In the preparation of the first mixed powder for the first layer of the CAM layer, the W ratio in the first mixed powder was set to 0.7 mol%. The particles in the obtained first CAM powder were first CAM particles (Li(Li 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.007 )O2,W concentration: 0.7mol%, average particle size D 50 The thickness was 10 μm.
[0090] [Example 7] The secondary battery of Example 7 was fabricated using the same method as the secondary battery of Example 1, except that the ratio of the thickness of the second layer to the thickness of each CAM layer (thickness 70 μm) was set to 60%.
[0091] [Example 8] The secondary battery of Example 8 was fabricated in the same manner as the secondary battery of Example 1, except that, in the formation of the CAM layer, a 70 μm thick CAM layer was formed on both sides of the positive electrode current collector from the first positive electrode slurry (containing the first CAM) without using the second positive electrode slurry.
[0092] [Example 9] The secondary battery of Example 9 was fabricated in the same manner as the secondary battery of Example 1, except that, in the formation of the CAM layer, a 70 μm thick CAM layer was formed on both sides of the positive electrode current collector from the second positive electrode slurry (containing the second CAM) without using the first positive electrode slurry.
[0093] [Example 10] In the preparation of the second CAM for the second layer, the secondary battery of Example 10 was manufactured using the same method as the secondary battery of Example 1, except that the preparation of the second mixed powder and the subsequent firing treatment were not performed.
[0094] [Example 11] The secondary battery of Example 11 was fabricated in the same manner as the secondary battery of Example 1, except for the following: In the preparation of the second mixed powder for the second layer of the CAM layer, the W ratio in the second mixed powder was set to 0.5 mol%. The particles in the obtained second CAM powder were second CAM particles (Li(Li 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.005 )O2,W concentration: 0.5mol%, average particle size D 50 The particle size was 4.0 μm.
[0095] [Example 12] The secondary battery of Example 12 was fabricated in the same manner as the secondary battery of Example 1, except that the ball milling described above was not performed on the second CAM for the second layer of the CAM layer.
[0096] <Compositional analysis of positive electrode active material> The composition of each positive electrode active material (CAM) in Examples 1 to 12 was confirmed using an ICP emission spectrometer (product name "SPS3520UV-DD", manufactured by Hitachi High-Tech Science Corporation).
[0097] <Particle size> For the first and second CAM particles in Examples 1-12, the average particle size D was measured using a laser diffraction particle size distribution analyzer (product name "MT3000II", manufactured by Microtrac-Bel). 50 The following measurements were taken. The results are shown in Table 1.
[0098] <Average particle strength> For the first and second CAM particles in Examples 1-12, the average particle strength was investigated as follows.
[0099] Particle strength was measured using the ENT-5 ultra-micro indentation hardness tester manufactured by Elionix Corporation. Specifically, first, a sample of CAM particle powder was fixed onto the stage of the device. Next, using the optical microscope equipped with the device, 10 arbitrary particles were selected from the sample, and the position coordinates of each particle on the stage were saved. For each particle, the diameter (d) was measured from the image captured by the camera equipped with the device. Next, the stage was moved directly below the flat indenter (downward-facing) set in the device. Then, based on the position coordinate data of a predetermined particle (target particle), the stage was finely adjusted so that the flat indenter was positioned directly above the particle. After that, the flat indenter was lowered onto the target particle on the stage, and the pressing force required to crush the particle was measured by the device. In this measurement, the amount of deformation of the particle was automatically measured, and the test force (pressing force) was applied to the particle while increasing it at a constant rate. Through this measurement, the test force P (MPa) at the point when crushing (rapid deformation) occurred in the particle was measured. Next, the crushing strength St (MPa) was calculated from the test force P and the particle diameter d (μm) based on the following formula (2) shown in JIS Z 8844 (2019). Then, the average value of the crushing strength St obtained for 10 particles was calculated as the average particle strength (MPa). These values are shown in Table 1.
[0100] St = 2.8P / πd 2 ...(2)
[0101] <Average circularity> The average circularity of the first and second CAM particles in Examples 1-12 was investigated as follows.
[0102] First, the circularity of the CAM particles (powder) to be measured was analyzed using the Morphologi 4 particle image analyzer (Malvern Panalytical). Specifically, the circularity (4πS / L) was analyzed for each of 50 particles arbitrarily selected from the powder. 2 The area of the particle (where S is the area and L is the perimeter of the particle image) was measured, and then the average circularity of 50 particles was calculated. This was defined as the average circularity. The values are shown in Table 1.
[0103] <Amount of coating elements> For CAM particles (first CAM particle, second CAM particle) in Examples 1-12 that contained tungsten (W), the presence of W as a surface element was confirmed by LA-ICP-MS analysis. In CAM particles prepared as described above, the higher the ratio of W (coating element) to the constituent metal elements (Ni, Co, Mn), the higher the ratio of W (coating element) on the surface. For CAM particles containing W, the ratio of W to the total amount of constituent metal elements (Ni+Co+Mn) is shown in Table 1 as the amount of coating element (mol%).
[0104] <Energy Density> The energy density of each secondary battery in Examples 1 to 12 was investigated as follows.
[0105] First, under conditions of 25°C, the current density of the secondary battery was kept constant (0.2 mA / cm²). 2 The battery is charged with a constant current until the voltage reaches 4.18V, and then the current density is set to 0.04mA / cm² at a constant voltage (4.18V). 2 The battery was charged at a constant voltage until it reached a constant current density (0.2 mA / cm²) under conditions of 25°C. Next, the secondary battery was charged at a constant current density (0.2 mA / cm²). 2 The discharge capacity (discharge energy) was measured by discharging at a constant current until the voltage reached 3.48V. The energy density (Wh / L) of the secondary battery was then calculated by dividing the discharge capacity (Wh) by the volume (L) of the secondary battery. Table 1 shows the relative values for the energy density of each secondary battery, with the energy density of the secondary battery in Example 8 set to 100.
[0106] <Gas generation amount in storage test> For each of the secondary batteries in Examples 1 to 12, the amount of gas generated was investigated by conducting storage tests as follows.
[0107] First, the volume (initial volume) of the secondary battery was measured using the Archimedes method. Fluorinert was used as the liquid in the Archimedes method. Next, under conditions of 25°C, the current density of the secondary battery was kept constant (0.2 mA / cm²). 2 The battery is charged with a constant current until the voltage reaches 4.2V, and then the current density is set to 0.04mA / cm² at a constant voltage (4.2V). 2 The batteries were charged at a constant voltage until the desired temperature was reached. Next, the charged batteries were stored in a constant temperature bath at 60°C for 5 days. Then, the batteries were allowed to cool in an environment of 25°C. After cooling, the volume (volume after storage test) of the batteries was measured using the Archimedes method under the same conditions as when the initial volume was measured. The difference (mL) between the volume after storage test and the initial volume was calculated and defined as the gas generation amount. Table 1 shows the relative values of the gas generation amount for each battery, with the gas generation amount of the battery in Example 8 set to 100.
[0108] [Table 1]
[0109] As shown in Table 1, among the secondary batteries of Examples 1 to 12, the secondary battery of Example 8 had the highest gas generation. This is thought to be because the CAM layer of the secondary battery of Example 8 (consisting of a single layer containing CAM particles with low average particle strength) experienced the most particle cracking during the CAM layer rolling process. Among the secondary batteries of Examples 1 to 12, the secondary battery of Example 9 had the lowest energy density. This is thought to be because the CAM layer of the secondary battery of Example 9 (consisting of a single layer containing CAM particles with high average particle strength) had low packing efficiency of the CAM particles. The secondary battery of Example 10 had the second highest gas generation after Example 8. Possible reasons for this include increased particle cracking during the CAM layer rolling process due to insufficient particle strength in the second layer (the second CAM particles do not have a coating element), and reduced resistance to side reactions that cause gas generation. The secondary battery of Example 11 had the third highest gas generation after Examples 8 and 10. One possible reason for this is that the insufficient amount of coating elements in the second CAM particles in the second layer (where the amount of coating elements in the second CAM particles is the same as that in the first CAM particles of the first layer) induced a lack of particle strength, leading to an increase in particle cracking during the CAM layer rolling process. The secondary battery in Example 12, like the secondary battery in Example 11, had the third highest amount of gas generation after Examples 8 and 10. One possible reason for this is that the average circularity of the second CAM particles in the second layer of the CAM layer of the secondary battery in Example 12 was low, resulting in insufficient particle slipperiness. This increased the effective load on the particles during the CAM layer rolling process, leading to an increase in particle cracking.
[0110] In contrast to these, the secondary batteries of Examples 1 to 7 achieved both high energy density and suppression of gas generation during high-temperature storage tests. This is thought to be due to a combination of factors: the second CAM particles in the second layer have a higher average particle strength than the first CAM particles in the first layer, suppressing press cracking of the second CAM particles during the CAM layer rolling process; the second CAM particles have a higher average circularity, ensuring slipability between them during the same process; the first CAM particles in the first layer have a lower average particle strength and are more flexible than the second CAM particles in the second layer, allowing the first layer to function as a cushion during the same process; and the first CAM particles are more easily deformed by press loads and thus more easily made highly packable than the second CAM particles.
[0111] As described above, the following configurations are examples of specific embodiments of the technology disclosed herein.
[0112] Section 1: A secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, The positive electrode comprises a current collector and a positive electrode active material layer on the current collector. The positive electrode active material layer includes a first layer and a second layer, wherein the first layer is located between the current collector and the second layer. The first layer comprises first positive electrode active material particles, The aforementioned second layer contains second positive electrode active material particles, The average particle strength of the second positive electrode active material particles is higher than the average particle strength of the first positive electrode active material particles and is 190 MPa or higher. A secondary battery in which the average circularity of the second positive electrode active material particles is 0.95 or higher.
[0113] Section 2: The secondary battery according to item 1, wherein the average particle strength of the first positive electrode active material particles is 160 MPa or less.
[0114] Section 3: The secondary battery according to claim 1 or 2, wherein the second positive electrode active material particles have a surface layer enriched with at least one element selected from the group consisting of Group 6 and Group 13 elements.
[0115] Section 4: The secondary battery according to any one of claims 1 to 3, wherein the proportion of the element selected from the group 6 and group 13 elements to the total amount of Ni, Co and Mn in the second positive electrode active material particles is 0.8 mol% or more and 3.0 mol% or less.
[0116] Section 5: The secondary battery according to any one of items 1 to 4, wherein the selected element is tungsten.
[0117] Item 6: The secondary battery according to any one of claims 1 to 5, wherein the proportion of the element selected from the group 6 and group 13 elements to the total amount of Ni, Co and Mn in the first positive electrode active material particles is less than 0.8 mol%.
[0118] Section 7: The secondary battery according to any one of items 1 to 6, wherein the ratio of the thickness of the second layer to the total thickness of the positive electrode active material layer is 5% or more and 65% or less.
[0119] Section 8: The average particle size D of the first positive electrode active material particles 50 A secondary battery as described in any one of items 1 to 7, wherein the diameter is between 5 μm and 18 μm.
[0120] Section 9: The average particle size D of the second positive electrode active material particles 50 A secondary battery as described in any one of items 1 to 8, wherein the diameter is between 3 μm and 15 μm.
[0121] Section 10: The positive electrode active material constituting the first positive electrode active material particles and / or the second positive electrode active material particles is a material with the composition formula Li(Li a Ni x Co y Mn z M α A secondary battery according to any one of items 1 to 9, which is a lithium composite oxide having a composition represented by the formula O2 [wherein -0.1≦a≦0.1, 0.7≦x≦1, 0≦y≦0.3, 0≦z≦0.3, x+y+z=1, 0≦α≦0.1, and M is at least one element selected from the group consisting of B, Al, Mg, Ca, Ti, V, Cr, Ga, Zr, Nb, Mo, In, Hf, Ta, W, Tl].
[0122] Although specific examples of the present invention have been described in detail above, these are merely illustrative and do not limit the scope of the claims. The technologies described in the claims include various modifications and changes to the specific examples illustrated above. [Explanation of symbols]
[0123] 100 Secondary battery 110 Battery Case 111 Safety valve 120 Electrode body 10 positive electrode 11. Positive electrode current collector (current collector) 12 Cathode active material layer 12A 1st layer 12B 2nd layer 20 negative electrode 21 Negative electrode current collector 22 Negative electrode active material layer 30 Separators 130 Positive terminal 131 Positive electrode current collector plate 140 Negative terminal 141 Negative electrode current collector plate
Claims
1. A secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, The positive electrode comprises a current collector and a positive electrode active material layer on the current collector. The positive electrode active material layer includes a first layer and a second layer, wherein the first layer is located between the current collector and the second layer. The first layer contains first positive electrode active material particles, The aforementioned second layer contains second positive electrode active material particles, The average particle strength of the second positive electrode active material particles is higher than the average particle strength of the first positive electrode active material particles and is 190 MPa or higher. A secondary battery in which the average circularity of the second positive electrode active material particles is 0.95 or higher.
2. The secondary battery according to claim 1, wherein the average particle strength of the first positive electrode active material particles is 160 MPa or less.
3. The secondary battery according to claim 1, wherein the second positive electrode active material particles have a surface layer enriched with at least one element selected from the group consisting of Group 6 and Group 13 elements.
4. The secondary battery according to claim 3, wherein the proportion of the element selected from the group 6 and group 13 elements to the total amount of Ni, Co and Mn in the second positive electrode active material particles is 0.8 mol% or more and 3.0 mol% or less.
5. The secondary battery according to claim 3, wherein the selected element is tungsten.
6. The secondary battery according to claim 3, wherein the proportion of the element selected from the group 6 and group 13 elements to the total amount of Ni, Co and Mn in the first positive electrode active material particles is less than 0.8 mol%.
7. The secondary battery according to claim 1, wherein the ratio of the thickness of the second layer to the total thickness of the positive electrode active material layer is 5% or more and 65% or less.
8. The average particle size D of the first positive electrode active material particles 50 The secondary battery according to claim 1, wherein the particle size is 5 μm or more and 18 μm or less.
9. The average particle size D of the second positive electrode active material particles 50 The secondary battery according to claim 1, wherein the particle size is 3 μm or more and 15 μm or less.
10. The positive electrode active material constituting the first positive electrode active material particles and / or the second positive electrode active material particles is a material with the composition formula Li(Li a Ni x Co y Mn z M α )O 2 A secondary battery according to any one of claims 1 to 9, wherein the lithium composite oxide has a composition represented by the formula [wherein -0.1 ≤ a ≤ 0.1, 0.7 ≤ x ≤ 1, 0 ≤ y ≤ 0.3, 0 ≤ z ≤ 0.3, x + y + z = 1, 0 ≤ α ≤ 0.1, and M is at least one element selected from the group consisting of B, Al, Mg, Ca, Ti, V, Cr, Ga, Zr, Nb, Mo, In, Hf, Ta, W, Tl].
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2023167298A